GAMBARAN FUNGSI KOGNITIF PADA PASIEN PASCA STROKE DI POLIKLINIK SARAF RSUD ARIFIN ACHMAD PROVINSI RIAU - Muslamiyah Hanas; Enny Lestari; Eni Karmila Asni (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTStroke is vascular disorders caused by occlusions or ruptures of the brain vessels. Cognitive impairment is results of the occurrence of stroke. This study aimed to describe the cognitive functions of post stroke patients in the Neurology Polyclinic of RSUD Arifin Achmad Riau Province.This study was descriptive study with cross sectional approach. The instrument in this research was Montreal Cognitive Assessment – Indonesian version (MoCA-INA). Samples of the study were post stroke patients who visited Neurology Polyclinic of RSUD Arifin Achmad Riau Province in the period of November – December 2015.This study used consecutive sampling method with total number was 41 respondents. The results showed that 92,68% of post stroke patients had cognitive impairment with the highest percentage at age >65 years old (34,14%), male (65,85%), education time ≤ 12 year (56,10%), ischemic stroke (78,05%), and stroke period >6 months (75,61%). As a conclusion, most of the post stroke patients in the Neurology Polyclinic of RSUD Arifin Achmad Riau Province showed cognitive impairments.Keywords: stroke, cognitive function, MoCA-INA.